Cardiovascular Programming During and After Diabetic Pregnancy: Role of Placental Dysfunction and IUGR - Langmia, Immaculate M.; Kräker, Kristin; Weiss, Sara E.; Haase, Nadine; Schütte, Till; Herse, Florian; Dechend, Ralf (Frontiers in Endocrinology, 2019)
Intrauterine growth restriction (IUGR) which is defined as fetal weight below the 10th percentile for gestational age is a global health challenge due to high mortality and morbidity amongst affected neonates. It is a multifactorial condition caused by maternal, fetal, placental and genetic confounders. Babies born of diabetic pregnancies are usually large for gestational age but under certain conditions whereby prolonged uncontrolled hyperglycemia leads to placental dysfunction, the outcome of the pregnancy is an intrauterine growth restricted fetus with clinical features of malnutrition. Research shows that placental dysfunction leads to undernutrition and hypoxia, which triggers gene modification in the developing fetus due to fetal adaptation to adverse utero environmental conditions. These in-utero gene modification results in future cardiovascular programming in postnatal and adult life. Research investigations that aim to widen our understanding on the molecular mechanisms and pathological pathways involved in fetal programming due to IUGR are ongoing. There is a need for development of effective preventive and therapeutic strategies for the management of growth-restricted infants. Information on the mechanisms involved in utero epigenetic modification leading to development of cardiovascular disease in adult life will increase our understanding and allow the identification of susceptible individuals as well as the design of targeted prevention strategies. This article aims to systematically review the latest molecular mechanisms involved in the pathogenesis of IUGR in cardiovascular programming. Animal models of IUGR that used nutrient restriction and hypoxia to mimic the clinical condition in humans of reduced flow of nutrients and oxygen to the fetus will be discuss in terms of cardiac remodeling and epigenetic programming of cardiovascular disease. Experimental evidence of long-term fetal programming due to IUGR will also be included.